Mapping of the viral shunt across widespread coccolithophore blooms using metabolic biomarkers - Constanze Kuhlisch; Guy Schleyer; J. Michel Flores; Flora Vincent; Karine Labadie; Marine Vallet; Daniella Schatz; Assaf Vardi (Proceedings of the National Academy of Sciences, 2026)
The viral shunt is a fundamental ecosystem process which diverts the flux of organic carbon fixed through photosynthesis during algal bloom events from heterotrophic grazers to bacteria. Through the extracellular release of metabolites, lytic viral infections supply 2 to 10% of photosynthetically fixed carbon in the ocean for bacterial respiration. Despite its significance for the carbon cycle, we lack tools to detect the viral shunt in the natural environment and assess its ecological impact. Here, we investigated the use of exometabolites as biomarkers for the viral shunt by applying molecular, metabolomics, and oceanographic tools to study bloom dynamics of the cosmopolitan microalga Gephyrocapsa huxleyi (formerly Emiliania huxleyi ) across the Atlantic Ocean, spanning four biogeochemical provinces between Iceland and Patagonia. We mapped the distinct metabolic footprint of its viral infections using exo- and endometabolomics and detected nineteen organohalogen metabolites across the blooms, showing their global distribution. A time-resolved comparison of particulate and dissolved metabolite pools during an induced mesocosm bloom revealed that virocells—actively infected host cells—were the source of the halogenated metabolites. Three trichloro-iodo metabolites were present during the demise of all virus-infected oceanic blooms, highlighting them as suitable metabolic biomarkers for the viral shunt. The environmental stability of these halometabolites in the dissolved organic matter pool over a few days can recapitulate viral infections at earlier stages of phytoplankton bloom succession. The chloro-iodo metabolites thereby expand the existing repertoire of metabolic biomarkers for viral infections at sea and may advance efforts to trace the biogeochemical impact of alga–virus interactions in the ocean.